Animal Exploitation in Prehistoric Southeastern Iran: Faunal Remains from Tepe Yahya and Tepe Gaz Tavila-R 37, 5500-3000 B.C. - Meadow, Richard Henry (1986)
Ph.D. Dissertation; 905 p. Order No. DA8704479; DissAbstr 47/11 (May 1987) 4120-A.